FDM3D printing long-acting noctilucent material and preparation method thereof

By adding luminous materials, modified polyhydroxybutyrate and anhydride modified montmorillonite to the polylactic acid matrix, the problems of low tensile strength, poor flame retardant performance and lack of luminous materials in FDM technology are solved, and the coordinated improvement of high tensile strength, good flame retardant performance and long-term luminous effect are achieved.

CN119775738AInactive Publication Date: 2025-04-08YANGCHUN MOERGU NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411702553.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When using polylactic acid as the main material in the prior art to FDM technology for 3D printing, there are problems such as low tensile strength, poor flame retardant performance, and lack of luminous materials that cannot obtain long-term luminous effects.

Method used

Polylactic acid is used as the main material and luminous materials are added, and modified polyhydroxybutyrate and anhydride modified montmorillonite are introduced. Through the synergistic effect of each component, the tensile strength and oxygen index of the material are improved, while achieving long-term luminous effects.

Benefits of technology

While achieving long-term luminous effects, the tensile strength and oxygen index of 3D printing materials are significantly improved, and the flame retardant performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of 3D printing materials, and particularly relates to an FDM 3D printing long-acting noctilucent material and a preparation method thereof. The polylactic acid is used as a main body material, the noctilucent material is added, meanwhile, the modified polyhydroxybutyrate and the anhydride modified montmorillonite are introduced, and through the synergistic effect of all the components, the tensile strength and the oxygen index of the 3D printing material are improved while the long-acting noctilucent effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printing materials, and in particular relates to an FDM 3D printing long-lasting luminous material and a preparation method thereof. Background Art

[0002] 3D printing is a new rapid prototyping method based on three-dimensional mathematical models. It mainly prepares different products by printing different materials layer by layer. 3D printing technology has been widely used in many fields such as construction, packaging, medical treatment and food. Fused deposition modeling (FDM) printing technology uses the hot melt and adhesive properties of thermoplastic materials. Under the control of computer software programs, it is extruded into filaments through a nozzle and then stacked layer by layer. Its printing materials are mainly polymers, including polylactic acid, polybutylene succinate, polycaprolactone, polybutylene adipate / terephthalate and polyhydroxybutyrate.

[0003] The invention patent (publication number CN105778484B) discloses a modified nylon material and printing method for 3D printing using FDM technology. The invention first uses a mixer to mix nylon resin and a tackifying nucleating agent, and then uses screw extrusion, granulation, wire drawing and other process technologies to obtain a modified nylon material that can be directly used for FDM printing. The molded parts obtained by FDM printing have excellent mechanical properties, good dimensional stability and low cost after simple post-processing. This patented technology mainly uses modified nylon as the main material for FDM technology, and does not solve the problems of low tensile strength, poor flame retardant performance, and lack of luminous materials in the prior art when using polylactic acid as the main material for 3D printing FDM technology. The problem that the long-lasting luminous effect cannot be obtained.

[0004] Therefore, how to use polylactic acid as the main material, add luminous materials to achieve a long-lasting luminous effect, and at the same time introduce modified components to improve the tensile strength and oxygen index of FDM3D printing materials has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a FDM 3D printing long-lasting luminous material and a preparation method thereof, aiming to solve the problems of low tensile strength, poor flame retardant properties, and lack of luminous materials that make it impossible to obtain a long-lasting luminous effect when polylactic acid is used as the main material in the prior art for FDM technology of 3D printing.

[0006] The present invention uses polylactic acid as the main material and adds luminous material, and introduces modified polyhydroxybutyrate and anhydride-modified montmorillonite at the same time. Through the synergistic effect of each component, the tensile strength and oxygen index of the 3D printing material are improved while achieving a long-lasting luminous effect.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows: A first aspect of the present invention provides a method for preparing a long-lasting luminous material by FDM 3D printing, comprising the following steps: Step S1: adding 20-30 parts of citric acid, 45-50 parts of ethylenediamine, 2-4 parts of soda lime and 1-2 parts of magnesium chloride to 150-200 parts of deionized water by weight, stirring for 40-60 minutes, and then reacting at 160-180° C. for 6-8 hours to obtain a mixed solution; cooling the mixed solution to room temperature, filtering, and dialyzing to obtain a dialysate; adding 80-100 parts of polyvinyl alcohol and 10-20 parts of nano-magnesium hydroxide to 150-200 parts of the dialysate, stirring and dispersing for 1-2 hours, and drying the precipitate after centrifugation to obtain a luminous material; Step S2: In parts by weight, 60-70 parts of polylactic acid, 30-40 parts of polyhydroxybutyrate, 8-12 parts of montmorillonite, 4-6 parts of luminous material, 1-3 parts of diphenyl dihydrazide sebacic acid, 1-3 parts of plasticizer and 0.6-0.8 parts of antioxidant are placed in a high-speed mixer for blending, and then transferred to a twin-screw extruder for extrusion molding to obtain FDM3D printing long-lasting luminous material.

[0008] The luminous material uses citric acid as a small molecule carbon to prepare a solid fluorescent carbon quantum dot material with high fluorescence intensity and a long service life. At the same time, the introduction of magnesium into the luminous material can capture the excitation energy and then transfer it to the luminescent center, thereby enhancing the excited state of the luminescent center and further improving the fluorescence intensity. At the same time, the nano-magnesium hydroxide in the luminous material decomposes at high temperature and forms a dense protective layer covering the surface of the material to prevent the transfer of oxygen and heat. At the same time, the released water vapor can dilute the combustible gas, reduce the combustion rate, and obtain a good flame retardant effect.

[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0010] As a preferred technical solution of the present invention, the polyhydroxybutyrate is a modified polyhydroxybutyrate; the preparation method of the modified polyhydroxybutyrate comprises: adding 2 to 4 parts of chitosan to 100 to 120 parts of an acetic acid aqueous solution with a mass concentration of 10%, stirring for 6 to 8 hours to obtain a chitosan solution; adding 5 to 10 parts of polyhydroxybutyrate microspheres, 2 to 4 parts of polycarbodiimide and 2 to 4 parts of N-hydroxysuccinimide to 200 to 300 parts of dimethyl sulfoxide, stirring for 10 to 12 hours, then adding 100 to 120 parts of the chitosan solution, stirring for 12 to 16 hours at 1800 to 2000 rpm, and centrifuging to obtain a precipitate; dispersing 5 to 10 parts of the precipitate in 80 to 100 parts of deionized water, then adding 1 to 3 parts of antimony chloride and 0.6 to 0.8 parts of sodium chloride, stirring for 20 to 24 hours, centrifuging and washing, and freeze-drying to obtain the modified polyhydroxybutyrate.

[0011] As a preferred technical solution of the present invention, the preparation method of the polyhydroxybutyrate microspheres comprises: adding 2 to 4 parts of polyhydroxybutyrate to 30 to 40 parts of chloroform by weight, stirring at 1200 to 1500 rpm for 6 to 8 hours to obtain a polyhydroxybutyrate solution, adding 30 to 40 parts of the polyhydroxybutyrate solution to 80 to 100 parts of a polyvinyl alcohol aqueous solution with a mass concentration of 1%, stirring for 4 to 6 hours, and then ultrasonically dispersing for 40 to 60 minutes to obtain an emulsion, allowing the emulsion to stand overnight, and then freeze-drying to obtain polyhydroxybutyrate microspheres.

[0012] Modified polyhydroxybutyrate contains antimony chloride, which can promote the formation of a carbon layer on the surface of the material at high temperature, prevent the transfer of oxygen and heat, reduce combustion, and improve flame retardant properties; in addition, antimony ions absorb the energy of excitation light, transition from the ground state to the excited state, and then return to the ground state through non-radiative transition, while emitting fluorescence, thereby increasing the fluorescence intensity of the material.

[0013] As a preferred technical solution of the present invention, the montmorillonite is anhydride-modified montmorillonite; the preparation method of the anhydride-modified montmorillonite comprises: adding 80 to 90 parts of chlorosilane-modified montmorillonite to 200 to 300 parts of tetrahydrofuran by weight for a second ultrasonic dispersion for 40 to 50 minutes, then adding 25 to 30 parts of 4-hydroxyphthalic anhydride and 5 to 8 parts of sodium hydride at 0 to 4° C., and reacting at 25 to 30° C. for 24 to 30 hours to obtain anhydride-modified montmorillonite.

[0014] As a preferred technical solution of the present invention, the preparation method of chlorosilane-modified montmorillonite comprises: adding 80 to 90 parts of montmorillonite to 200 to 300 parts of anhydrous ethanol by weight for a first ultrasonic dispersion for 30 to 40 minutes, then adding 80 to 100 parts of methyltrichlorosilane, stirring at 25 to 35° C. for 16 to 20 hours to obtain chlorosilane-modified montmorillonite.

[0015] The anhydride molecules in the anhydride-modified montmorillonite will be inserted into the interlayer of montmorillonite, react with the cations between the montmorillonite layers through chemical bonds, increase the interlayer distance of montmorillonite, and improve its dispersibility in the polylactic acid matrix. At the same time, the anhydride can combine with the hydroxyl group of polylactic acid to form a three-dimensional network structure, strengthen the internal network of the composite material, and improve the tensile strength of the material.

[0016] Preferably, the plasticizer is selected from any one of tributyl citrate, acetyl tributyl citrate, and epoxy soybean oil, or a combination of at least two thereof.

[0017] Preferably, the antioxidant is selected from any one of 2,6-di-tert-butyl-p-cresol, octyl diphenyl phosphite, and didodecyl thiodipropionate, or a combination of at least two thereof.

[0018] Preferably, the blending treatment conditions include: a blending speed of 400-1000 r / min, and a blending time of 10-20 min.

[0019] Preferably, the extrusion molding processing conditions include: an extrusion temperature of 180-210° C. and a twin-screw extruder speed of 500-800 r / min.

[0020] The second aspect of the present invention provides an FDM 3D printing long-lasting luminous material prepared by the method described in the first aspect.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The matrix of the FDM 3D printing long-lasting luminous material of the present invention is polylactic acid resin, which has active groups such as ester group, carboxyl group, and hydroxyl group, which can be combined with the amino group in the modified polyhydroxybutyrate and the anhydride in the modified montmorillonite, respectively, and serve as a bridge to connect the modified polyhydroxybutyrate and the anhydride-modified montmorillonite, constructing a network interconnection structure, and effectively improving the tensile strength of the material.

[0022] (2) The hydroxyl groups on the polyvinyl alcohol molecular chains contained in the luminous material of the present invention can form hydrogen bonds with the polar groups of polylactic acid and polyhydroxybutyrate, thereby enhancing interfacial interactions and improving compatibility. At the same time, the magnesium element is introduced through the luminous material. The magnesium-based material will absorb a large amount of heat when decomposed at high temperatures, thereby reducing the surface temperature of the material and slowing down the combustion process. The antimony element is introduced through the modified polyhydroxybutyrate. The antimony-based material can promote the formation of a carbon layer on the surface of the material at high temperatures, thereby preventing the transfer of oxygen and heat. The silicon element is introduced through the anhydride-modified montmorillonite. The silicon element has a low surface energy and is easily migrated to the surface of the build-up film to form a silicon-containing protective layer, thereby improving the thermal stability of the material and improving the oxygen index of the material through the synergistic effect of magnesium-antimony-silicon.

[0023] (3) The luminous material of the present invention uses citric acid as a small molecule carbon to prepare a solid fluorescent carbon quantum dot material with high fluorescence intensity and long service life. At the same time, the introduction of magnesium element into the luminous material can capture the excitation energy, and then transfer it to the luminescent center, thereby enhancing the excited state of the luminescent center and further improving the fluorescence intensity. In addition, nano-magnesium hydroxide decomposes at high temperature and forms a dense protective layer covering the surface of the material to prevent the transfer of oxygen and heat. At the same time, the released water vapor can dilute the combustible gas, reduce the combustion rate, and obtain a good flame retardant effect.

[0024] (4) The modified polyhydroxybutyrate of the present invention contains antimony chloride, which can promote the formation of a carbon layer on the surface of the material at high temperature, prevent the transfer of oxygen and heat, reduce combustion, and improve flame retardancy; in addition, antimony ions absorb the energy of excitation light, transition from the ground state to the excited state, and then return to the ground state through non-radiative transition, while emitting fluorescence, thereby improving the fluorescence intensity of the material.

[0025] (5) The anhydride molecules in the anhydride-modified montmorillonite of the present invention will be inserted into the interlayer of montmorillonite, react with the cations between the montmorillonite layers through chemical bonds, increase the interlayer distance of montmorillonite, and improve its dispersibility in the polylactic acid matrix. At the same time, the anhydride can combine with the hydroxyl group of polylactic acid to form a three-dimensional network structure, strengthen the internal network of the composite material, and improve the tensile strength of the material. DETAILED DESCRIPTION

[0026] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0027] The sources of some components in the embodiments and comparative examples are as follows: Commercially available polylactic acid, product number 38534, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; Commercially available polyhydroxybutyrate, product number PA78171, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Commercially available montmorillonite, model WSG-PN06, was purchased from Shanghai Wanzhao Fine Chemical Co., Ltd.; Commercially available fluorescent material, model HT-811, was purchased from Huangshan Jiajia Fluorescent Material Co., Ltd.; Sebacate diphenyl dihydrazide, CAS No. 35658-27-6, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; Tributyl citrate, product number T105179, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Acetyl tributyl citrate, product number PA86972, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Epoxidized soybean oil, product number PA41772, was purchased from Shanghai Chuangsai Technology Co., Ltd.; 2,6-di-tert-butyl-p-cresol, product number D104363, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Octyl diphenyl phosphite, CAS No. 3164-55-4, purchased from Jinjinle Chemical Co., Ltd.; Didodecyl thiodipropionate, product number PA30588, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Citric acid, CAS No. 77-92-9, purchased from Shanghai Huayuan Century Trading Co., Ltd.; Ethylenediamine, CAS No. 107-15-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Soda lime, CAS No. 8006-28-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Magnesium chloride, CAS No. 7786-30-3, was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; Polyvinyl alcohol, product number PA73430, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Nano magnesium hydroxide, brand VK-MHT01, purchased from Hangzhou Wanjing New Materials Co., Ltd.; Chloroform, CAS No. 67-66-3, purchased from Sinopharm Chemical Reagent Co., Ltd.; Chitosan, product number M29342, was purchased from Shanghai Myrel Biochemical Technology Co., Ltd.; Acetic acid, CAS No. 64-19-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Polycarbodiimide, brand GX-3, purchased from Jiangsu Aoshijia Material Technology Co., Ltd.; N-Hydroxysuccinimide, CAS No. 6066-82-6, purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; Dimethyl sulfoxide, CAS No. 67-68-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Antimony chloride, CAS No. 10025-91-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Sodium chloride, CAS No. 7647-14-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Methyltrichlorosilane, CAS No. 75-79-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Tetrahydrofuran, CAS No. 109-99-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; 4-Hydroxyphthalic anhydride, CAS No. 27550-59-0, purchased from Jinde Chemical Technology (Shanghai) Co., Ltd.; Sodium hydride, CAS No. 7646-69-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0028] Preparation of modified polyhydroxybutyrate: (1) In parts by weight, 4 parts of polyhydroxybutyrate were added to 40 parts of chloroform, and stirred at 1200 rpm for 8 hours to obtain a polyhydroxybutyrate solution. 40 parts of the polyhydroxybutyrate solution were added to 100 parts of a 1% polyvinyl alcohol aqueous solution and stirred for 6 hours, and then ultrasonically dispersed for 60 minutes to obtain an emulsion. The emulsion was allowed to stand overnight and then freeze-dried to obtain polyhydroxybutyrate microspheres. (2) In parts by weight, 4 parts of chitosan were added to 120 parts of 10% acetic acid aqueous solution, and stirred for 8 hours to obtain a chitosan solution; 10 parts of polyhydroxybutyrate microspheres, 4 parts of polycarbodiimide and 4 parts of N-hydroxysuccinimide were added to 300 parts of dimethyl sulfoxide, and stirred for 12 hours, and then 120 parts of the chitosan solution were added, and stirred at 2000 rpm for 12 hours, and centrifuged to obtain a precipitate; 10 parts of the precipitate were dispersed in 100 parts of deionized water, and then 3 parts of antimony chloride and 0.8 parts of sodium chloride were added, stirred for 24 hours, centrifuged for washing, and freeze-dried to obtain modified polyhydroxybutyrate.

[0029] Preparation of anhydride-modified montmorillonite: (1) By weight, 90 parts of montmorillonite were added to 300 parts of anhydrous ethanol for a first ultrasonic dispersion for 40 minutes, and then 100 parts of methyltrichlorosilane were added and stirred at 35°C for 16 hours to obtain chlorosilane-modified montmorillonite. (2) By weight, 90 parts of chlorosilane-modified montmorillonite were added to 300 parts of tetrahydrofuran for a second ultrasonic dispersion for 50 minutes, and then 30 parts of 4-hydroxyphthalic anhydride and 8 parts of sodium hydride were added at 0°C and reacted at 25°C for 30 hours to obtain anhydride-modified montmorillonite. Example 1

[0030] This embodiment provides a method for preparing a long-lasting luminous material by FDM 3D printing, comprising the following steps: Step S1: adding 30 parts of citric acid, 50 parts of ethylenediamine, 4 parts of soda lime and 2 parts of magnesium chloride to 200 parts of deionized water by weight, stirring for 60 minutes, and then reacting at 180° C. for 6 hours to obtain a mixed solution; cooling the mixed solution to room temperature, filtering, and dialyzing to obtain a dialysate; adding 100 parts of polyvinyl alcohol and 20 parts of nano-magnesium hydroxide to 200 parts of the dialysate, stirring and dispersing for 2 hours, and drying the precipitate after centrifugation to obtain a luminous material; Step S2: In parts by weight, 70 parts of polylactic acid, 40 parts of modified polyhydroxybutyrate, 12 parts of anhydride modified montmorillonite, 6 parts of luminous material, 3 parts of diphenyl dihydrazide sebacate, 3 parts of tributyl citrate and 0.8 parts of 2,6-di-tert-butyl-p-cresol are placed in a high-speed mixer for blending (blending speed is 1000 r / min, blending time is 10 min), and then transferred to a twin-screw extruder for extrusion molding (extrusion temperature is 210°C, twin-screw extruder speed is 800 r / min) to obtain FDM3D printing long-lasting luminous material. Example 2

[0031] This embodiment provides a method for preparing a long-lasting luminous material by FDM 3D printing, comprising the following steps: Step S1: adding 20 parts of citric acid, 45 parts of ethylenediamine, 2 parts of soda lime and 1 part of magnesium chloride to 150 parts of deionized water by weight, stirring for 40 minutes, and then reacting at 160° C. for 8 hours to obtain a mixed solution; cooling the mixed solution to room temperature, filtering, and dialyzing to obtain a dialysate; adding 80 parts of polyvinyl alcohol and 10 parts of nano-magnesium hydroxide to 150 parts of the dialysate, stirring and dispersing for 1 hour, and drying the precipitate after centrifugation to obtain a luminous material; Step S2: In parts by weight, 60 parts of polylactic acid, 30 parts of modified polyhydroxybutyrate, 8 parts of anhydride modified montmorillonite, 4 parts of luminous material, 1 part of diphenyl sebacate dihydrazide, 1 part of acetyl tributyl citrate and 0.6 parts of diphenyl phosphite are placed in a high-speed mixer for blending (blending speed is 400r / min, blending time is 20min), and then transferred to a twin-screw extruder for extrusion molding (extrusion temperature is 180°C, twin-screw extruder speed is 500r / min) to obtain FDM3D printing long-lasting luminous material. Example 3

[0032] This embodiment provides a method for preparing a long-lasting luminous material by FDM 3D printing, comprising the following steps: Step S1: adding 25 parts of citric acid, 48 parts of ethylenediamine, 3 parts of soda lime and 2 parts of magnesium chloride to 180 parts of deionized water by weight, stirring for 50 minutes, and then reacting at 170° C. for 7 hours to obtain a mixed solution; cooling the mixed solution to room temperature, filtering, and dialyzing to obtain a dialysate; adding 90 parts of polyvinyl alcohol and 15 parts of nano-magnesium hydroxide to 180 parts of the dialysate, stirring and dispersing for 2 hours, and drying the precipitate after centrifugation to obtain a luminous material; Step S2: In parts by weight, 65 parts of polylactic acid, 35 parts of modified polyhydroxybutyrate, 10 parts of anhydride modified montmorillonite, 5 parts of luminous material, 2 parts of diphenyl dihydrazide sebacic acid, 2 parts of epoxy soybean oil and 0.7 parts of didodecyl thiodipropionate are placed in a high-speed mixer for blending (blending speed is 800r / min, blending time is 15min), and then transferred to a twin-screw extruder for extrusion molding (extrusion temperature is 190°C, twin-screw extruder speed is 600r / min) to obtain FDM3D printing long-lasting luminous material.

[0033] Comparative Example 1 This comparative example provides a method for preparing a 3D printing material, which differs from Example 1 in that a commercially available fluorescent material is used to replace the luminous material, a commercially available polyhydroxybutyrate is used to replace the modified polyhydroxybutyrate, and a commercially available montmorillonite is used to replace the anhydride-modified montmorillonite.

[0034] Comparative Example 2 This comparative example provides a method for preparing a 3D printing material, which differs from comparative example 1 in that a luminous material is used to replace a commercially available fluorescent material.

[0035] Comparative Example 3 This comparative example provides a method for preparing a 3D printing material, which differs from comparative example 1 in that modified polyhydroxybutyrate is used to replace commercially available polyhydroxybutyrate.

[0036] Comparative Example 4 This comparative example provides a method for preparing a 3D printing material, which differs from comparative example 1 in that anhydride-modified montmorillonite is used to replace commercially available montmorillonite.

[0037] Comparative Example 5 This comparative example provides a method for preparing a 3D printing material, which differs from Example 1 in that a commercially available fluorescent material is used to replace the luminous material.

[0038] Comparative Example 6 This comparative example provides a method for preparing a 3D printing material, which differs from Example 1 in that commercially available polyhydroxybutyrate is used instead of modified polyhydroxybutyrate.

[0039] Comparative Example 7 This comparative example provides a method for preparing a 3D printing material, which differs from Example 1 in that commercially available montmorillonite is used to replace the anhydride-modified montmorillonite.

[0040] The performance of the 3D printing materials provided in the above embodiments and comparative examples was tested, and the testing method was as follows: The fluorescence intensity test was conducted using Tianjin Gangdong F-280 fluorescence spectrophotometer with an ultraviolet light wavelength of 360nm; the tensile strength was tested in accordance with the requirements of ISO 527-2-2012 Plastics Tensile Properties Test; the oxygen index was tested in accordance with the requirements of GB / T 2406.2-2009 Plastics Oxygen Index Method for Determination of Combustion Behavior Part 2: Room Temperature Test.

[0041] The above performance test data is shown in Table 1.

[0042] Table 1 Performance test results

[0043] From the above content, it can be seen that the present invention uses polylactic acid as the main material and adds luminous material, and introduces modified polyhydroxybutyrate and anhydride modified montmorillonite to prepare FDM3D printing long-lasting luminous material (Examples 1~3), whose fluorescence intensity is 559~564, tensile strength is 26.8~27.3MPa, and oxygen index is 33.4~33.9%.

[0044] Compared with Example 1, the commercially available fluorescent material is used to replace the luminous material, the commercially available polyhydroxybutyrate is used to replace the modified polyhydroxybutyrate, and the commercially available montmorillonite is used to replace the anhydride modified montmorillonite, then the fluorescence intensity becomes smaller, the tensile strength decreases, and the oxygen index decreases (Comparative Example 1); compared with Comparative Example 1, the luminous material is used to replace the commercially available fluorescent material, the fluorescence intensity becomes larger, and the oxygen index increases (Comparative Example 2); compared with Comparative Example 1, the modified polyhydroxybutyrate is used to replace the commercially available polyhydroxybutyrate, the fluorescence intensity becomes larger, and the oxygen index increases (Comparative Example 3); Compared with Comparative Example 1, the use of anhydride-modified montmorillonite to replace the commercially available montmorillonite increases the tensile strength (Comparative Example 4); compared with Example 1, the use of commercially available fluorescent material to replace the luminous material reduces the fluorescence intensity and reduces the oxygen index (Comparative Example 5); compared with Example 1, the use of commercially available polyhydroxybutyrate to replace modified polyhydroxybutyrate reduces the fluorescence intensity, reduces the tensile strength, and reduces the oxygen index (Comparative Example 6); compared with Example 1, the use of commercially available montmorillonite to replace the anhydride-modified montmorillonite reduces the tensile strength and reduces the oxygen index (Comparative Example 7).

[0045] In summary, the present invention uses polylactic acid as the main material and adds luminous material, and introduces modified polyhydroxybutyrate and anhydride-modified montmorillonite. Through the synergistic effect of each component, the tensile strength and oxygen index of the 3D printing material are improved while achieving a long-lasting luminous effect.

[0046] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a long-lasting luminous material for FDM 3D printing, characterized in that: The following steps are involved: Step S1: adding 20-30 parts of citric acid, 45-50 parts of ethylenediamine, 2-4 parts of soda lime and 1-2 parts of magnesium chloride to 150-200 parts of deionized water by weight, stirring for 40-60 minutes, and then reacting at 160-180° C. for 6-8 hours to obtain a mixed solution; cooling the mixed solution to room temperature, filtering, and dialyzing to obtain a dialysate; adding 80-100 parts of polyvinyl alcohol and 10-20 parts of nano-magnesium hydroxide to 150-200 parts of the dialysate, stirring and dispersing for 1-2 hours, and drying the precipitate after centrifugation to obtain a luminous material; Step S2: by weight, 60-70 parts of polylactic acid, 30-40 parts of polyhydroxybutyrate, 8-12 parts of montmorillonite, 4-6 parts of luminous material, 1-3 parts of sebacic acid diphenyl dihydrazide, 1-3 parts of plasticizer and 0.6-0.8 parts of antioxidant are placed in a high-speed mixer for blending, and then transferred to a twin-screw extruder for extrusion molding to obtain FDM3D printing long-lasting luminous material; The polyhydroxybutyrate is a modified polyhydroxybutyrate; the preparation method of the modified polyhydroxybutyrate comprises: adding 2 to 4 parts of chitosan to 100 to 120 parts of an acetic acid aqueous solution with a mass concentration of 10%, stirring for 6 to 8 hours to obtain a chitosan solution; adding 5 to 10 parts of polyhydroxybutyrate microspheres, 2 to 4 parts of polycarbodiimide and 2 to 4 parts of N-hydroxysuccinimide to 200 to 300 parts of dimethyl sulfoxide, stirring for 10 to 12 hours, then adding 100 to 120 parts of the chitosan solution, stirring for 12 to 16 hours at 1800 to 2000 rpm, and centrifuging to obtain a precipitate; dispersing 5 to 10 parts of the precipitate in 80 to 100 parts of deionized water, then adding 1 to 3 parts of antimony chloride and 0.6 to 0.8 parts of sodium chloride, stirring for 20 to 24 hours, centrifuging and washing, and freeze-drying to obtain the modified polyhydroxybutyrate; The montmorillonite is anhydride-modified montmorillonite; the preparation method of the anhydride-modified montmorillonite comprises: adding 80 to 90 parts of chlorosilane-modified montmorillonite to 200 to 300 parts of tetrahydrofuran by weight, performing a second ultrasonic dispersion for 40 to 50 minutes, then adding 25 to 30 parts of 4-hydroxyphthalic anhydride and 5 to 8 parts of sodium hydride at 0 to 4° C., reacting at 25 to 30° C. for 24 to 30 hours, and obtaining anhydride-modified montmorillonite.

2. The method for preparing a FDM 3D printing long-lasting luminous material according to claim 1, characterized in that: The preparation method of the polyhydroxybutyrate microspheres comprises: adding 2 to 4 parts of polyhydroxybutyrate to 30 to 40 parts of chloroform by weight, stirring at 1200 to 1500 rpm for 6 to 8 hours to obtain a polyhydroxybutyrate solution, adding 30 to 40 parts of the polyhydroxybutyrate solution to 80 to 100 parts of a polyvinyl alcohol aqueous solution with a mass concentration of 1%, stirring for 4 to 6 hours, and then ultrasonically dispersing for 40 to 60 minutes to obtain an emulsion, allowing the emulsion to stand overnight, and then freeze-drying to obtain polyhydroxybutyrate microspheres.

3. The method for preparing a FDM 3D printing long-lasting luminous material according to claim 1, characterized in that: The preparation method of the chlorosilane-modified montmorillonite comprises: adding 80-90 parts of montmorillonite to 200-300 parts of anhydrous ethanol by weight for a first ultrasonic dispersion for 30-40 minutes, then adding 80-100 parts of methyltrichlorosilane, stirring at 25-35° C. for 16-20 hours, and obtaining the chlorosilane-modified montmorillonite.

4. The method for preparing a FDM 3D printing long-lasting luminous material according to claim 1, characterized in that: The plasticizer is selected from any one of tributyl citrate, acetyl tributyl citrate, and epoxy soybean oil, or a combination of at least two of them.

5. The method for preparing a FDM 3D printing long-lasting luminous material according to claim 1, characterized in that: The antioxidant is selected from any one of 2,6-di-tert-butyl-p-cresol, octyl diphenyl phosphite, and didodecyl thiodipropionate, or a combination of at least two thereof.

6. The method for preparing a FDM 3D printing long-lasting luminous material according to claim 1, characterized in that: The blending treatment conditions include: a blending speed of 400-1000 r / min and a blending time of 10-20 min.

7. The method for preparing a FDM 3D printing long-lasting luminous material according to claim 1, characterized in that: The extrusion molding processing conditions include: an extrusion temperature of 180-210° C. and a twin-screw extruder speed of 500-800 r / min.

8. A FDM3D printing long-lasting luminous material, characterized in that: Prepared according to the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • A modified nylon material applied to fdm technology for 3D printing and its printing method

    CN105778484B

  • Preparation method of carbon dot having high fluorescent quantum yield

    CN103045242A

  • Manufacturing method of fluorescent 3D printing material

    CN110105734A

  • Fluorescently-labeled degradable 3D printing resin as well as preparation method and application thereof

    CN112980169A

  • Noctilucent PLA / PBAT wire for 3D printing and preparation method of noctilucent PLA / PBAT wire

    CN113354932A

Cited By

  • Laser edge sealing strip and production process thereof

    CN120424392A